(3TQM GdehGQjK ef GdfGaY GdefJNH ef GdTQGFYs - (3eLghds
(3ChdgG (B:s
... (3dCf GdfHj Udi Gddg Ydjg hSde cGf bO HjfGg Ydi eG gh eTghQ ePchQ aj GdbQBf MjK dbhdg SHMGfg adeG bVi RjO efgG hWQG RhLfGcgG dFdG jchf Ydi GdeDefjf MQL aj CRhGL (B...s
(3BNQgG (B:s
.. (3hajg JQOO hhLg GdJQOO Cfg de jhLO Ydjg Odjd ef QhGjI Ch JfRjd abO CaJi GdTjNGf (B... (3Ydi JYjjf CMO GdCeQjf hdG jSJOd HGJOGFgeG Ydi Cfg eTcd GdCeQ hGdJQOO VYja(B.s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3abg GdePGgH GdCNQis